2020
DOI: 10.3390/membranes10120445
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Pattern Geometry on Nanofiltration Threshold Flux

Abstract: Colloidal fouling can be mitigated by membrane surface patterning. This contribution identifies the effect of different pattern geometries on fouling behavior. Nanoscale line-and-groove patterns with different feature sizes were applied by thermal embossing on commercial nanofiltration membranes. Threshold flux values of as-received, pressed, and patterned membranes were determined using constant flux, cross-flow filtration experiments. A previously derived combined intermediate pore blocking and cake filtrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…One strategy is patterned membranes. Patterned membranes, often reported for fouling control, typically involve fabrication methods such as phase separation micromolding, , thermal embossing/nanoimprinting, ,, and 3D printing. , Previous studies have constructed patterns such as grooved lines, ,, pillars, prism, and pyramid with dimensions ranging from tens of nanometers to hundreds of micrometers. These patterned membranes, when used as substrates, are expected to create aqueous/organic interfaces with regular/periodical morphological features.…”
Section: Classification Of Crumpled Morphologies Their Formation Mech...mentioning
confidence: 99%
“…One strategy is patterned membranes. Patterned membranes, often reported for fouling control, typically involve fabrication methods such as phase separation micromolding, , thermal embossing/nanoimprinting, ,, and 3D printing. , Previous studies have constructed patterns such as grooved lines, ,, pillars, prism, and pyramid with dimensions ranging from tens of nanometers to hundreds of micrometers. These patterned membranes, when used as substrates, are expected to create aqueous/organic interfaces with regular/periodical morphological features.…”
Section: Classification Of Crumpled Morphologies Their Formation Mech...mentioning
confidence: 99%
“…The above-mentioned studies on patterned membranes have revealed that the ratio between the pattern size and the length scale of other parameters such as particle size and channel height has a significant influence on fouling mitigation relying on the hydrodynamics of a feed fluid due to a specific membrane pattern. Computational fluid dynamics (CFD) simulations can be used to elucidate the influence of surface features on the hydrodynamics and concentration polarization near the membrane surfaces [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surface patterned membranes are a versatile platform that can overcome limitations of feed spacers, as well as promote separation performance and antifouling propensity of pressure-driven membranes in water treatment and desalination applications [1,2]. Membrane fouling and concentration polarization are among main obstacles that are challenging ultimate process efficiency, besides increasing energy demands and operation costs [3].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, alignment of surface microstructures with respect to feed flow direction was shown to influ-ence the desalination performance [7,11,13]. Nevertheless, recent publications have emphasized that such effects are substantially influenced by several operating parameters (e.g., pattern design, crossflow velocity and size of solutes) [2,4,6,7].…”
Section: Introductionmentioning
confidence: 99%